Acid-catalysed cellulose pyrolysis at low temperatures - Long, Yu; Yu, Yun; Chua, Yee Wen; Wu, Hongwei (Elsevier Ltd, 2017)
© 2016 Elsevier LtdThis study reports the pyrolysis of the acid-impregnated cellulose at 50–325 °C. The presence of acid is found to significantly change cellulose pyrolysis mechanism. While the pyrolysis of raw cellulose mainly proceeds with depolymerisation reactions, the pyrolysis of the acid-impregnated cellulose is dominantly contributed by dehydration reactions. The acid impregnation process seems to weaken the hydrogen bonding networks in cellulose, promoting the formation of glucose oligomers as reaction intermediates. Due to the presence of acid in the reaction intermediates, the glucose oligomers are rapidly hydrolysed to glucose, especially at low temperatures (i.e., 100 °C) where the evaporation of produced water (via dehydration) is slow. The results also suggest that glucose is subsequently dehydrated to low molecular weight compounds at increased temperatures. The highly dehydrated cellulose further suppresses the depolymerisation reactions, resulting in a low levoglucosan yield during acid-catalysed pyrolysis of cellulose. The highly dehydrated cellulose also favours char formation likely via furanic structures which are finally transformed into aromatic structures at temperatures >300 °C.